DEXMEDETOMIDINE FOR REGIONAL ANESTHESIA: AN UMBRELLA REVIEW - Dossymbek, Dayana (Nazarbayev University School of Medicine, 2024)
Objective: To determine the perioperative effect of dexmedetomidine as a pharmacological adjunct to the regional anesthesia in adult surgical patients. Introduction: Dexmedetomidine is an α-sympathomimetic drug, which has a high selectivity and specificity for α2-adrenoceptor of noradrenergic neurons and affects the modulation of pain perception. Multiple systematic reviews and meta-analyses are associated with advantages of administering dexmedetomidine as an adjuvant drug for adult surgical patients with regional anesthesia. Inclusion criteria: In this umbrella analysis, relevant systematic reviews and meta-analyses involving adult patients (older than 18 years) undergoing surgery and receiving preoperative regional anesthesia with dexmedetomidine as an adjuvant drug and published before January 2024 are eligible for inclusion. Methods: 22 relevant articles were screened and 14 of them were excluded after full-text assessment due to failing to meet all inclusion criteria or/and meeting one of the exclusion criteria. The remaining eight studies were critically appraised and primary and secondary outcomes of the articles were assessed. Results: Perineural administration of dexmedetomidine in brachial plexus block for upper limb surgery prolongs the duration of analgesia compared to local anesthetics alone. Discussion: Further investigations on the topic would help make umbrella review more comprehensive and result in recommendations of a high statistical value and credibility.
Keywords: type of access: gated access